HOW DOES STUDENT INVOLVEMENT IN EXTRACURRICULAR ACTIVITIES IMPACT THE OVERALL COLLEGE EXPERIENCE? - Samandar Shirinboyev; Fozilbek Orzibekov (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
College life is a pivotal period of scholastic and personal development guided by experience within and beyond the official classroom context. Extracurricular activities (ECAs) are an integral component of the non-classroom environment widely believed to have an impact on students’ entire college life. In its first section, the article discusses the point of initiation through which the involvement of students in ECAs influences the preliminary phases of college experience. I specifically examine the ECA’s role in social integration, creating required non-academic skills and establishing a sense of belonging to the university community. Based on a literature and conceptual review of the relevant literature, I place into perspective how participation in ECAs fosters peer relationship development, relieves feelings of loneliness, and enhances student ability to cope with the campus social environment. Furthermore, it explains how engagement in different activities provides good chances for the acquisition of skills, including leadership, teamwork, communication, and time management all key skills for academic resilience and professional success. I conclude by framing the significant, early contribution of ECAs to students’ attachment to their college and the development of a foundation essential to a positive, integrated collegiate experience, paving the way for further examination of long-term effects in subsequent parts.